RECONSTRUCTION OF SCIENTIFIC INVESTIGATION IN INDONESIA - Teguh Prihmono (Jurnal Pembaharuan Hukum, 2018)
The purpose of this study is to analyze the process of scientific investigation, the empowerment of scientific investigation by investigators, obstacles faced and finding scientific investigation based ideal of justice. This study uses empirical juridical approach that is related to the professional investigators and forensic laboratory examiner in conducting scientific investigations, also used a qualitative approach of the source of primary data and secondary data, then analyzed diskriftif with sestematika sentence further discussion is concluded. The problem is analyzed with proof theory and the theory of legal certainty so that it can be concluded find scientific investigation based on the ideal of justice.